Evaluasi Dimensi Tiang Pancang Dermaga di Daerah Pesisir Kabupaten Kolaka dengan Mempertimbangkan Pengaruh Likuifaksi - Minmahddun, A.; Mangidi, U. (REKONSTRUKSI TADULAKO: Civil Engineering Journal on Research and Development, 2024)
The pier in the coastal area of Kolaka Regency plays a crucial role in the distribution of goods and economic enhancement. However, the risk of liquefaction due to earthquakes threatens the stability and safety of the pier structure. This study aims to evaluate the dimensions of the pier piles considering the effects of liquefaction. The research methodology includes the analysis of liquefaction potential using the NCEER method, axial load capacity analysis using the Briaud method, and deflection analysis using the Broms method. Foundation analysis under liquefaction conditions is simplified by assuming the SPT values in the liquefied soil layer to be zero. Standard Penetration Test (SPT) data were used to assess soil conditions at the pier location. The analysis results indicate that the sand layer at a depth of 6-12 meters has a high potential for liquefaction, primarily due to the high content of coarse grains and a fine particle percentage of 15%. The increase in peak ground acceleration (PGA) in the Sulawesi region also amplifies the potential for liquefaction. The foundation analysis without considering liquefaction shows that the pile dimensions with a depth of 25 meters meet the design criteria, although deflection approaches the permissible limit. However, under liquefaction conditions, there is a slight reduction in axial load capacity (3%), but the pile deflection increases beyond the allowable limit. To mitigate the risk of liquefaction and ensure the safety of the pier, it is recommended to extend the pile depth to 28 meters.